2013
DOI: 10.1161/circheartfailure.112.971424
|View full text |Cite
|
Sign up to set email alerts
|

A Cardiomyopathy in a Patient With Limb Girdle Muscular Dystrophy Type 2A

Abstract: L imb girdle muscular dystrophy (LGMD) is a muscular dystrophy with predominantly proximal distribution of weakness that spares the distal, facial, and extraocular muscles early in the course of the disease. Cardiac muscle may be affected, which may manifest as hypertrophic/dilated cardiomyopathy and cardiac dysrhythmias. Significant cardiac involvement has been documented frequently in LGMD2C-F, 2I, and LGMD1B forms of the disease, rarely in the LGMD1C and 2B subtypes, and thus far have not been reported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…A few case reports have suggested cardiac involvement. For example, Okere et al reported that a 23‐year‐old patient with calpainopathy had cardiomyopathy . Of the 2 autopsy cases reported by Hashiguchi et al, 1 with an incomplete right bundle branch block showed myocardial atrophy without any other causative disease; however, no degeneration or necrosis was found in the myocardium of this patient.…”
Section: Discussionmentioning
confidence: 71%
“…A few case reports have suggested cardiac involvement. For example, Okere et al reported that a 23‐year‐old patient with calpainopathy had cardiomyopathy . Of the 2 autopsy cases reported by Hashiguchi et al, 1 with an incomplete right bundle branch block showed myocardial atrophy without any other causative disease; however, no degeneration or necrosis was found in the myocardium of this patient.…”
Section: Discussionmentioning
confidence: 71%
“… 49) In isolated case reports, however, CCDs, LVHT, and heart failure have been reported. 50) As with LGMD2A, CI in LGMD2B is usually mild 51) 52) or absent. 53) Only rarely may patients present with dCMP.…”
Section: Resultsmentioning
confidence: 99%
“…In advanced disease stages, a deficiency in diaphragm function, resulting in reduced forced vital capacity and overt respiratory insufficiency, is frequently observed . Cardiac involvement has only been reported occasionally …”
Section: Selection Of Candidate Patients For Lgmd2a Diagnosismentioning
confidence: 99%